تحولات الشكل في مواجهة المعنى - رشيد، نجوى صديق (Natural Sciences Publishing, 2017)
لعل واحدة من أهم الإشكاليات التي ألفتها نظرية الفن هي ظاهرة التحولات السريعة التي طرأت على الفن عموماً وعلى الشكل الفني خصوصاً فقد سعت النظرية وكذلك فعل النقد إلى تناول هذه التحولات بالتفسير والتحليل وربطها بالظاهرة الفنية التي تنشئ في إطار نسق ما، وبقدر ارتباط الأخير بالأساليب والتيارات الفنية المختلفة من جانب وعلاقتها بإطارها التأريخي من جانب آخر، كان لابد أن تندفع بقوة إلى الأمام جدلية التآصر لتطور ثنائية الأدوار الوظائفية والأشكال الفنية وكأنها أطوار تصاعدية أوصلت الشكل إلى منعطفات حادة في مشهدية تحولاته وتغييراته النوعية محكوما بضرورات واقعية وتأريخية.
Without a doubt, the artist always seeks to get a response from the viewers, he builds a form that carries different messages, which leads us to say that the plastic art communication is addressed to the viewers and open to those who questioned it, and this process is done by perception and understanding the structural elements of the form how the artist's ideas were expressed and how his message was embodied, The contents behind the form are not realized unless these elements are interconnected in one structure expressing itself on the visible surface so that the viewer tries to decipher the symbols, signs and linguistic signs. It is a process of recognizing the visual experience associated with color, space and other elements of expression. All this necessarily requires a certain effort from the viewer touch the aesthetic experience through the communication process, and it may become more complicated with the appreciation of modern art, which needs for an education that may be somewhat different from the prevailing way of receiving and appreciating, which requires the availability of new cognitive habits in the sense that it requires another kind of culture, feeling and perception, because it all deepens our perceptions and expands its horizons to be able to produce different readings of different art to achieve an aesthetic experience from different kind.
Keywords: فلسفة الفنون -- الفنون التشكيلية -- اللوحات الفنية -- النقد الفني